Zebrafish Embryo Infection Model to Investigate Pseudomonas aeruginosa Interaction With Innate Immunity and Validate New Therapeutics - Pont, Stéphane; Blanc-Potard, Anne-Béatrice (Frontiers in Cellular and Infection Microbiology, 2021)
The opportunistic human pathogen Pseudomonas aeruginosa is responsible for a variety of acute infections and is a major cause of mortality in chronically infected cystic fibrosis (CF) patients. Considering P. aeruginosa intrinsic and acquired resistance to currently used antibiotics, new therapeutic strategies against this pathogen are urgently needed. Whereas virulence factors of P. aeruginosa are well characterized, the interplay between P. aeruginosa and the innate immune response during infection remains unclear. Zebrafish embryo is now firmly established as a potent vertebrate model for the study of infectious human diseases, due to strong similarities of its innate immune system with that of humans and the unprecedented possibilities of non-invasive real time imaging. This model has been successfully developed to investigate the contribution of bacterial and host factors involved in P. aeruginosa pathogenesis, as well as rapidly assess the efficacy of anti-Pseudomonas molecules. Importantly, zebrafish embryo appears as the state-of-the-art model to address in vivo the contribution of innate immunity in the outcome of P. aeruginosa infection. Of interest, P. aeruginosa pathogenesis, innate immune response, and treatment evaluation can also be monitored in CF embryos.